ОСОБЛИВОСТІ Я-КОНЦЕПЦІЇ КОНФЛІКТНИХ ПІДЛІТКІВ - Ярошенко, Світлана Іванівна (My University, 2023)
Особливості Я-концепції конфліктних підлітків на сьогодні важлива тема для обговорення. Тому що Я-концепція конфліктних підлітків характеризується складною взаємодією ідентичності, самооцінки, емоційних переживань, механізмів подолання труднощів і сприйняттям себе як жертви або винуватця конфлікту.
The features of the self-concept of conflicted adolescents are an important topic for discussion today. The self-concept of conflicted adolescents is characterized by a complex interaction of identity, self-esteem, emotional experiences, mechanisms for overcoming difficulties, and perception of oneself as a victim or instigator of conflict.
Keywords: Я-концепція; конфліктні підлітки; особливості; розвиток; конфліктність